Fatwa and Virtual Reality: The Maqāṣid al-Sharīʿah Perspective on the Metaverse and Virtual Life - Ahmad; Najib, Muhammad; Makkarateng, Ma'adul Yaqien (MUI Sulawesi Selatan, 2025)
This study aims to explore the relevance of Maqāṣid al-Sharīʿah in facing the challenges and opportunities presented by the Metaverse, as well as offering an adaptive Islamic legal framework for the virtual world. In an increasingly complex digital era, challenges such as the spread of false information, identity manipulation, digital addiction, economic exploitation, and negative impacts on family relationships have become major issues that require a Shariah-based approach. A literature analysis method was used to review previous relevant and in-depth studies on Maqāṣid al-Sharīʿah, digital technology, and contemporary issues in the Metaverse. The results showed that Maqāṣid al-Sharīʿah could be flexibly applied in five main dimensions, namely protection of religion (al-dīn), life (al-nafs), reason (al-‘aql), offspring (al-nasl), and property (al-māl). Protection of religion includes the development of virtual spaces that support interactive education and da'wah. The dimension of life includes the psychological well-being of technology users through moderation and digital literacy, while reason emphasises the importance of information verification to prevent hoaxes and manipulation. The protection of offspring focuses on Islamic-based platforms to support children education and strengthen family values. The property dimension underscores the need for Shariah regulation in digital economic transactions to ensure fairness and transparency. In conclusion, Maqāṣid al-Sharīʿah is not only relevant but also capable of becoming an ethical and normative foundation for creating an ethical, inclusive Metaverse ecosystem consistent with Islamic values. This study also opens up opportunities for further investigations on the practical implementation of Islamic law in the virtual world.